Kolaborasi Stakeholder Lembaga Pendidikan Nonformal Mahad Tahfidzul Quran Darussalam Depok dalam Meningkatkan Akses dan Kualitas Pendidikan - Wiranda, Aditya; Khaeroh, Cholifatul; Nulhakim, Lukman (Samsara Institute Publisher, 2025)
Ma’had Tahfidzul Qur’an, as a nonformal Islamic educational institution, plays a crucial role in expanding access to religious education and nurturing the moral development of youth. However, challenges such as limited funding, infrastructure, and human resources remain prevalent. This study aims to explore how stakeholder collaboration involving institutional leaders, parents, community figures, private sector partners, and local government contributes to improving access and educational quality at Ma’had Tahfidzul Qur’an Darusalam Depok. Using a descriptive qualitative approach, data were gathered through field observation, in-depth interviews, and documentation review, then analyzed thematically. The findings reveal that collaboration is not merely administrative but is rooted in a shared sense of ownership and values. Parents are actively involved in students' learning progress, communities support religious and social programs, and external stakeholders contribute through training and infrastructure support. These collaborative efforts have significantly increased student enrollment, enhanced educational outcomes, and fostered public trust in the institution. The study concludes that well-managed stakeholder collaboration is a vital key to the success and sustainability of nonformal education. These insights offer a potential model for similar institutions aiming to build inclusive, community-based educational environments.